Spadkobiercy nazistowskiego okultyzmu. Powojenne ruchy neonazistowskie i ariozoficzne - Drozdowicz, Jarema (Polskie Towarzystwo Religioznawcze, 2010)
Jarema Drozdowicz – THE ANCESTORS OF NAZI OCCULTISM. NEONAZI AND ARIOSOPHIC MOVEMENTS AFTER 1945 The aim of this article is to show how the nazi esoteric tradition evolved after World War II and how these concepts were put into action by far right political movements in Europe and United States. Their ideological basis is linked to classical 19th esoteric concepts of ariosophy developed for example by Helena Blavatsky. These concepts are related to the cyclic view of history, the Aryan race and the issue of nation and culture. Authors like Savitri Devi or Miguel Serrano did not just shared this beliefs but also put the into action within neonazi movements. International ties between them and other far right and neonazi authors and intellectualso build a strong net-work of cooperation. Devi’s and Serrano’s theses were influential in these circles, especially after they had crystallized a systematic vision of the past the present world.